Comparison of Early Postoperative Pain between Lightweight Mesh and Heavyweight Mesh in Lichtenstein Hernia Repair for Geriatric Patients at Rumah Sakit Siloam Karawaci from January 2018 - December 2019 - Sidharta, Nicholas Axel; Irawan, Andry; Siregar, Jeremia Immanuel; Lugito, Nata Pratama Hardjo (Medicinus, 2022)
Background: Inguinal hernias are one of the most often cases in surgery. Inguinal hernias are usually found in males rather than females. There are two types of meshes in inguinal hernia repairs: heavyweight and lightweight mesh. There were still a lot of differences in the outcome of each mesh that was used. Therefore, with various different post operative pain results from past research, the author expresses an interest to conduct a research on this topic towards geriatric patients.Methods: In this cross-sectional comparative study, 45 patients using heavyweight mesh and 45 patients using lightweight mesh herniorrhaphy with Lichtenstein technique in inguinal hernias at RS Siloam Karawaci Lippo Village and RSU were reviewed retrospectively. Patient's data were taken from medical record using purposive-sampling method. Early Postoperative pain on day 1 until 7 were classified following the Visual Analogue Scale (VAS). Incidence of postoperative infection and seroma were assessed in both groups. Collected samples will be processed using Pearson's Chi-Squared test.Result: This study shows that there is a significant difference between the use of lightweight mesh in reducing moderate early postoperative pain for men above the age of 60 years old (p = 0.025) rather than the use of heavyweight mesh. Incidence of other postoperative complications such as infection and seroma have no statistically difference between both groups.Conclusions: The use of lightweight mesh has the advantage in reducing early postoperative pain from herniorrhaphy using Lichtenstein technique rather than heavyweight mesh in men above 60 years old.